Study of bamboo flakes reinforced polymer composite material ignition and flame spread properties - Nor Adiba Farhanah Mhd Nor Bakri (2022)
A study on the bamboo reinforced composite materials ignition and flame spread properties had been conducted. Bamboo had been widely engineered for enhancing its material application, especially as architect building materials. Flammable property study is crucial in determining the fire hazardous of the material. The study is involving 5 types of materials (bamboo reinforced epoxy composite material, bamboo reinforced polyester resin, pure epoxy/ polyester resin matrix materials and raw bamboo). The materials tested under vertically and horizontally burn test, which accordance to ASTM D635 and ISO 3795. This study includes a vertical burning test to determine the entire flame time of the materials tested, as well as a horizontal burning test to investigate the burning rate and flame spread of the materials examined. Flammability property includes combustion time, flame dripping and burning rate. The flame spread of both composite materials increase as time and the flame period is significantly greater when bamboo flakes strengthen the resins. The average flame time of unsaturated polyester resin reinforced with bamboo flakes is 6.71 minutes and that of epoxy resin reinforced with bamboo flakes is 3.96 minutes. As for the average burning rate of unsaturated polyester resin reinforced with bamboo flakes and epoxy resin reinforced with bamboo flakes are 56.33 mm/min, 73.89 mm/min. The study findings provided a crucial information in determining the material application feasibility and flammability property improvement.